Rupture of the Thoracic Aorta due to Blunt Chest Trauma a Case Report - Altun, Gürcan; Yılmaz, Ahmet; Azmak, Ali Derya (The Bulletin of Legal Medicine, 1998)
Traumatic rupture of the thoracic aorta may occur in cases of blunt chest trauma. This case was brought to our hospital after being injured in a serious traffic accident. After about eight hours he died suddenly during nasogastric catheter application. In the autopsy, blunt head trauma injuries, profuse bleeding in neck and mediastinum, 1700 cc blood in the chest cavity, total rupture of the thoracic aorta just distal to the origin of subclavian artery and fracture of left femoral diaphysis with a large hematoma around it were seen. Key Words: Traffic accident, Chest trauma, Aortic rupture, Medical malpractice, Autopsy.